Numerical and Experimental Analysis of the Daughter Distribution in Liquid‐Liquid Stirred Tanks. Issue 11 (21st September 2021) - Maluta, Francesco; Buffo, Antonio; Marchisio, Daniele; Montante, Giuseppina; Paglianti, Alessandro; Vanni, Marco
Abstract: The drop size distributions (DSDs) of a dilute immiscible liquid‐liquid mixture were measured in a fully turbulent stirred tank operating at different impeller speeds. The results were used to infer the best daughter distribution function (DDF) leading to the best reproduction of the shape of the DSD. Bell‐shaped, U‐shaped, M‐shaped, and uniform statistical DDFs were studied, producing from two to four daughters from each breakup event. A simplified approach from the literature was adopted to solve the population balance equation that considers the spectrum of the turbulence inside the tank obtained from computational fluid dynamics simulations. The U‐shaped distribution producing four fragments better reproduces the shape of the experimental DSD in the studied system. Abstract : The influence of the fragment number and size distribution resulting from drop breakup in a liquid‐liquid mixture in a stirred tank on the final drop size distribution is studied from the numerical and the experimental point of view. The daughter distribution function shape and the number of droplets that better describe the experimental data are identified.